Fabrication of (Zr, Ti)B2–ZrN–BN composites through reactive spark plasma sintering of ZrB2 and TiN. (March 2022) - Ahmadi, Zohre; Shahedi Asl, Mehdi; Zakeri, Mohammad; Farvizi, Mohammad
Highlights: (Zr, Ti)B2 –ZrN–BN ceramic was fabricated using ZrB2 and TiN starting materials. A fully dense ZrB2 -based material was obtained by SPS and 5 wt% TiN additive. Solid solution formation and in-situ synthesis of nitrides were proven by SEM/XRD. Significant enhancement in mechanical properties was observed by addition of TiN. Abstract: Mechanical properties and sintering behavior of additive-free and TiN-doped ZrB2 ceramics were studied. Reactive spark plasma sintering method was applied for manufacturing of ceramics at 1850 °C for 6 min under 40 MPa. The impact of TiN addition on the microstructure evaluation, densification, and mechanical feathers was investigated. A porous monolithic ZrB2 with a relative density of 76.5 % was manufactured, while the introduction of 5 wt% TiN resulted in enhancement of relative density to 93.1 %. The formation of (Zr, Ti)B2 solid solution and in-situ h-BN and ZrN phases was proven by microstructural assessments and X-ray diffractometry. Minimizing the grain growth and improving the densification, as the results of TiN addition, led to enhancement in mechanical properties. The values of bending strength, fracture toughness, and Vickers hardness boosted from 187.6 MPa, 1.9 MPa.m ½, and 10.1 GPa for additive-free ZrB2 to 606.5 MPa, 4.5 MPa.m ½, and 18.8 GPa for (Zr, Ti)B2 –ZrN–BN composite.